Polymer film for biosensor and preparation method thereof
By doping hydrophobic crosslinked polymer microspheres in the polymer film, the degree of swelling of the polymer film when the temperature changes is reduced, the problem of high temperature sensitivity of traditional polymer films is solved, and the detection accuracy of glucose biosensors is improved .
Patent Information
- Application Number
- CN202411820990.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-02-18
Smart Images

Figure CN119463377A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biosensors, and more particularly to a polymer film for a biosensor and a preparation method thereof. Background Art
[0002] Biosensors are usually used to quickly detect certain specific chemicals in the human body. Among them, enzyme electrode sensors are commonly used, which can be used to detect glucose, urea, uric acid and a series of amino acid compounds.
[0003] Taking the in vivo implantable current sensor as an example, the working electrode usually includes a sensing layer that is in direct contact with the electrode conductive layer, and a membrane layer at the outermost layer of the sensing layer. The sensing layer usually includes an enzyme, an enzyme stabilizer, and a cross-linking agent. For an implantable glucose electrochemical sensor, the membrane at the outermost layer of the electrode is used to control the glucose concentration reaching the sensing layer; if the glucose sensor has no membrane layer, the glucose concentration reaching the sensing layer is the same as the glucose concentration in the body. When the glucose reaching the surface of the sensing layer is consumed, there is a certain linear relationship between the detected current value and the glucose concentration. However, when the glucose consumption capacity is limited by the electrochemical kinetics of the sensing layer, the output current value is no longer linearly related to the glucose concentration value reaching the surface of the sensing layer. In this case, the glucose concentration reaching the sensing layer can only be controlled by a diffusion control membrane. At this time, there is a fixed concentration difference between the glucose concentration inside and outside the membrane, and the sensing layer can detect a very high glucose concentration before saturation. Since the human skin temperature is greatly affected by the outside world, and temperature has a great influence on the diffusion flux of traditional polymer membranes, causing a large deviation in the detection accuracy of the sensor, a temperature calibration factor is usually added to compensate for the error caused by temperature changes, but not all polymer membranes have a good linear correlation in diffusion flux to temperature. In addition, the addition of temperature sensors increases the cost of the equipment on the one hand, and puts higher requirements on the algorithm on the other. Therefore, for glucose biosensors, it is of great significance to develop a temperature-sensitive and insensitive polymer membrane. Summary of the invention
[0004] In view of this, the main purpose of the present invention is to provide a method for preparing a polymer membrane for a biosensor. The polymer membrane obtained by the present invention can effectively reduce the degree of swelling caused by solvation during temperature rise, reduce the flux of solutes in the solvent when the temperature changes, thereby reducing its temperature sensitivity, and when used as the outer membrane of a glucose biosensor, it has a good glucose measurement linear range and temperature responsiveness.
[0005] To achieve the above object, the technical solution of the present invention is as follows:
[0006] A polymer membrane for a biosensor, the polymer membrane is a two-phase cross-linked polymer membrane, wherein the first phase is a polymer body, and the second phase is polymer microspheres, the polymer body is an amphiphilic cross-linked polymer, and the polymer microspheres are hydrophobic cross-linked polymers; the amphiphilic cross-linked polymer consists of a hydrophilic component, a hydrophobic component and a cross-linking agent A.
[0007] In the present invention, since the hydrophobic polymer microspheres have a low swelling degree in aqueous solution and a small volume change when the temperature changes, when the polymer microspheres are cross-linked with the polymer body, the swelling degree of the polymer membrane caused by solvation during the temperature rise process can be effectively reduced, and the flux of solutes in the solvent during temperature changes can be reduced, thereby reducing its temperature sensitivity! Moreover, when the polymer membrane is used as the outer membrane of a glucose oxidase-type biosensor, it has good temperature response performance and a good linear range of glucose measurement during the in vivo use of the glucose oxidase-type biosensor defined herein for glucose measurement.
[0008] Further, the hydrophobic monomer in the hydrophobic cross-linked polymer includes at least one of styrene, methyl methacrylate, glycidyl methacrylate, glycidyl acrylate, methyl acrylate, butyl methacrylate, butyl acrylate, ethyl methacrylate, ethyl acrylate, phenylethyl methacrylate, phenylethyl acrylate, phenoxyethyl methacrylate, phenoxyethyl acrylate, tert-butyl methacrylate, tert-butyl acrylate, 2-vinylpyridine, 4-vinylpyridine, ethoxyethyl methacrylate and ethoxyethyl acrylate.
[0009] Furthermore, the hydrophilic component is at least one of polyethylene glycol, polyethylene methacrylate, poly N-vinyl pyrrolidone, polyvinyl alcohol, polyacrylamide, poly N,N-dimethylacrylamide, polyacrylic acid, sodium polystyrene sulfonate, polyhydroxyethyl methacrylate, and polyhydroxyethyl acrylate.
[0010] Further, the hydrophobic component is at least one of polystyrene, polymethyl methacrylate, polymethyl acrylate, polybutyl methacrylate, polybutyl acrylate, polyethyl methacrylate, polyethyl acrylate, polyphenylethyl methacrylate, polyphenylethyl acrylate, polyphenoxyethyl methacrylate, polyphenoxyethyl acrylate, polytert-butyl methacrylate, polytert-butyl acrylate, poly-2-vinylpyridine, poly-4-vinylpyridine, polyethoxyethyl methacrylate and polyethoxyethyl acrylate.
[0011] Furthermore, the cross-linking agent A is one of polyethylene glycol diglycidyl ether, adipic acid, hexamethylenediamine or glutaraldehyde.
[0012] Furthermore, the hydrophilic component, the hydrophobic component and the crosslinking agent in the amphiphilic crosslinked polymer are polymerized in the form of random copolymerization, block copolymerization or graft copolymerization.
[0013] Furthermore, in the amphiphilic cross-linked polymer, the mass content of the cross-linking agent is 1% to 10%, the mass content of the hydrophilic component is 20% to 50%, and the mass content of the hydrophobic component is 40% to 79%.
[0014] Furthermore, the diameter of the polymer microspheres is 0.1um to 1um, preferably 0.2um to 0.5um.
[0015] A second object of the present invention is to provide a method for preparing any of the above-mentioned polymer films, comprising the following steps:
[0016] A. Preparation of polymer microspheres
[0017] 1) Add the hydrophobic monomer and crosslinking agent B into ultrapure water and blow high-purity nitrogen for 20-40 minutes to deoxygenate;
[0018] 2) Add a water-soluble initiator and stir to dissolve it;
[0019] 3) Place in a 70-90°C oil bath and heat with stirring for 20-30 hours;
[0020] 4) centrifuging, washing and drying the product to obtain a solid powder;
[0021] B. Introduction of amphiphilic cross-linked polymers
[0022] 1) dissolving the amphiphilic cross-linked polymer and the cross-linking agent in tetrahydrofuran, and shaking for 8-15 minutes to completely dissolve them;
[0023] 2) Add the prepared solid powder and perform ultrasonic treatment for 8-15 minutes to uniformly disperse the powder in the solution to obtain a polymer film.
[0024] Furthermore, in step A), the initiator is at least one of potassium persulfate and ammonium persulfate; the crosslinking agent B includes at least one of 1,4-divinylbenzene, 1,4-butanediol dimethacrylate, 1,3-propylene glycol dimethacrylate, 1,4-butanediol diacrylate, and 1,3-propylene glycol diacrylate.
[0025] Furthermore, in the polymer film, the mass content of the amphiphilic cross-linked polymer is 70% to 95%, and the mass content of the polymer microspheres is 5% to 30%. More preferably, the mass content of the amphiphilic cross-linked polymer is 80% to 90%, and the mass content of the polymer microspheres is 10% to 20%.
[0026] The present invention also aims to provide a glucose biosensor comprising any of the above-mentioned polymer films.
[0027] Specifically, the prepared polymer film can be coated on the substrate surface, i.e., the electrode surface, by spraying, ring coating, or dip-pulling, and dried to obtain a transparent film. When dip-pulling, the film is coated on the electrode surface, the dipping time is 3-6s, preferably 5s, and the two layers are dried for 2-5 minutes. 8-12 layers are coated to obtain a transparent film, and the preparation is completed by drying in a nitrogen environment for 40-60 hours.
[0028] Compared with the prior art, the present invention has the following advantages:
[0029] The polymer membrane provided by the present invention can effectively reduce the swelling degree of the polymer membrane caused by solvation during temperature rise by doping hydrophobic cross-linked polymer microspheres in the bulk polymer, reduce the flux of solutes in the solvent when the temperature changes, thereby reducing its temperature sensitivity, and when it is used as the outer membrane of a glucose biosensor, it has a good glucose measurement linear range and temperature responsiveness.
[0030] In addition, the electrochemical sensor membrane can be prepared from the polymer membrane of the present invention by simple dipping, pulling, spraying, spin coating, circle coating and other coating processes, which is conducive to industrial mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 Schematic diagram of the polymer membrane mechanism of the present invention; wherein A does not contain polymer microspheres; B contains polymer microspheres.
[0032] Figure 2 This is a scanning electron microscope photo of polymer microspheres.
[0033] Figure 3 This is the linearity test result of the glucose sensor.
[0034] Figure 4 This is the temperature coefficient test curve of sensing electrodes E1 and E2. DETAILED DESCRIPTION
[0035] Many specific details are set forth in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar modifications without violating the connotation of the present invention, so the present invention is not limited to the specific implementation disclosed below.
[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0037] Example 1
[0038] This example illustrates the preparation method of polymer microspheres S1.
[0039] Add 0.5g of styrene, 0.1g of 1,4-divinylbenzene, and 0.05g of glycidyl methacrylate to the reaction bottle in sequence, then add 50mL of ultrapure water, and blow high-purity nitrogen into the mixed solution for 30 minutes to remove oxygen. Add 0.01g of potassium persulfate, stir for 2 minutes to dissolve it, and then place it in a pre-heated 80℃ oil bath and continue stirring for 24 hours.
[0040] The white mixed system was poured into a centrifuge tube, and the speed was set to 10000 rpm. After centrifugation for 10 minutes, the supernatant was separated, ultrapure water was added, and ultrasonic dispersion was performed for 5 minutes, and then centrifugation was performed. The washing was repeated 3 times, and then dried in a vacuum drying oven at 60°C to obtain 0.46 g of white powder, namely, polymer microspheres S1, with a diameter of 300 nm.
[0041] The scanning electron microscope image is as follows Figure 2 shown.
[0042] Example 2
[0043] This example illustrates the preparation method of polymer microspheres S2.
[0044] Add 1.0g of methyl methacrylate, 0.4g of 1,4-butanediol dimethacrylate, and 0.1g of glycidyl methacrylate to the reaction bottle in sequence, then add 100mL of ultrapure water, and blow high-purity nitrogen into the mixed solution for 30 minutes to remove oxygen. Add 0.015g of potassium persulfate, stir for 2 minutes to dissolve it, and then place it in a pre-heated 80℃ oil bath and continue stirring for 24 hours.
[0045] The white mixed system was poured into a centrifuge tube, and the speed was set to 10000 rpm. After centrifugation for 10 minutes, the supernatant was separated, ultrapure water was added, and ultrasonic dispersion was performed for 5 minutes, and then centrifugation was performed. The washing was repeated 3 times, and then dried in a vacuum drying oven at 60°C to obtain 1.26 g of white powder, namely, polymer microspheres S2, with a diameter of 500 nm.
[0046] Example 3
[0047] This example illustrates the preparation method of polymer microspheres S3.
[0048] Add 1.0g of styrene, 0.2g of 1,4-divinylbenzene, and 0.1g of glycidyl methacrylate to the reaction bottle in sequence, then add 100mL of ultrapure water, and blow high-purity nitrogen into the mixed solution for 30 minutes to remove oxygen. Add 0.02g of potassium persulfate, stir for 2 minutes to dissolve it, and then place it in a pre-heated 80℃ oil bath and continue stirring for 8 hours.
[0049] The white mixed system was poured into a centrifuge tube, and the speed was set to 10000 rpm. After centrifugation for 10 minutes, the supernatant was separated, ultrapure water was added, and ultrasonic dispersion was performed for 5 minutes, and then centrifugation was performed. The washing was repeated 3 times, and then dried in a vacuum drying oven at 60°C to obtain 0.68 g of white powder, namely, polymer microspheres S3, with a diameter of 200 nm.
[0050] Example 4
[0051] This example illustrates a method for preparing a sensing electrode E1 containing a temperature-insensitive two-phase cross-linked polymer membrane of the present invention.
[0052] 0.5g of poly-(styrene-co-hydroxyethyl methacrylate) and 0.05g of polyethylene glycol diglycidyl ether were dissolved in 20mL of tetrahydrofuran solution and shaken for 10 minutes to completely dissolve it. In the poly-(styrene-co-hydroxyethyl methacrylate), the mass content of the hydrophilic component poly(hydroxyethyl methacrylate) was 30%, and the content of the hydrophobic component polystyrene was 70%. 0.1g of polymer microspheres S1 were added and ultrasonicated for 10 minutes to make them uniformly dispersed in the solution. The carbon-printed three-electrode system with glucose oxidase drop-coated was coated on the electrode surface by dipping and pulling. The dipping time was 5s, and the two layers were dried for 3 minutes. 10 layers were coated to obtain a transparent film with a thickness of about 40um. The preparation was completed by drying in a nitrogen environment for 48 hours to obtain a membrane sensing electrode E1.
[0053] In the same way, without adding polymer microspheres S1, a comparative sensing electrode E2 was also prepared.
[0054] The schematic diagram of the mechanism corresponding to E1 and E2 is shown in Figure 1 As shown, it can be seen that since the hydrophobic polymer microspheres have a low swelling degree in aqueous solution and a small volume change when the temperature changes, when the polymer microspheres are cross-linked with the polymer body, the swelling degree of the polymer membrane caused by solvation during the temperature rise process can be effectively reduced, and the flux of solutes in the solvent when the temperature changes can be reduced, thereby reducing its temperature sensitivity.
[0055] Example 5
[0056] This example illustrates a sensing electrode E3 comprising a temperature-insensitive two-phase cross-linked polymer membrane of the present invention.
[0057] The operation is similar to that of Example 4, except that S2 is used to replace S1 in Example 5, and the rest of the operations are the same. A membrane sensing electrode E3 is obtained.
[0058] Example 6
[0059] This example illustrates a sensing electrode E4 comprising a temperature-insensitive two-phase cross-linked polymer membrane of the present invention.
[0060] The operation is similar to that of Example 4, except that S3 is used to replace S1 in Example 6, and the rest of the operations are the same. A membrane sensing electrode E4 is obtained.
[0061] Example 7
[0062] This example illustrates a sensing electrode E5 comprising a temperature-insensitive two-phase cross-linked polymer membrane of the present invention.
[0063] The operation is similar to that of Example 4, except that poly-(methyl acrylate-co-hydroxyethyl acrylate) is used instead of poly-(styrene-co-hydroxyethyl methacrylate) in Example 7, and the rest of the operations are the same. A membrane sensing electrode E5 is obtained.
[0064] Example 8
[0065] This example illustrates the use of membranes produced by the present invention for performance evaluation of a glucose biosensor.
[0066] 1. Linearity test
[0067] The sensing electrode E1 was immersed in 32°C standard PBS buffer (pH 7.4, 150 mM NaCl), and the sensor was allowed to reach a stable current for 10 minutes. Glucose at concentrations of 2.2, 5.0, 10.0, 15.0, 20.0 and 25.0 was added to the solution to measure the linearity of the reaction.
[0068] The glucose concentration current curves of the sensing electrodes E2, E3 and E4 were tested in the same way.
[0069] 2. Temperature sensitivity test
[0070] The sensing electrode E1 was immersed in a 32°C standard PBS buffer (pH 7.4, 150mM NaCl), and the sensor reached a stable current after 10 minutes. Then, glucose with concentrations of 2.2, 5.0, 10.0, 15.0, 20.0, and 25.0 was added to the solution to measure the linearity of the reaction. The slope K value was calculated based on the curve fitting and recorded as the sensitivity value of the electrode.
[0071] Using the same method, the electrode sensitivity values at 34°C, 36°C, 37°C, 38°C and 40°C were tested respectively, and the linear relationship between the sensitivity value and temperature was calculated to obtain the rate of change △K1 of the electrode sensitivity value caused by unit temperature change.
[0072] The same method was used to test the glucose concentration current curve of the sensing electrode E2 at different temperatures, and the change rate △K2 of the sensitivity value of the sensing electrode E2 was calculated. By comparing the values of △K1 and △K2, the temperature sensitivity of the outer membrane was evaluated.
[0073] Figure 3 is a graph showing the relationship between glucose concentration and current intensity under 37° C. provided in an embodiment of the present invention; Figure 3 It can be seen that the five sensors E1, E2, E3, E4 and E5 have very good linearity between 2.2-25mM concentration.
[0074] Figure 4 It is the test response current curve of sensing electrodes E1 and E2 at different temperatures and different glucose concentrations.
[0075] Table 1 shows the test response current values of the sensing electrodes E1 and E2 at different temperatures and different glucose concentrations. By calculating △K1=0.080 and △K2=0.105, it can be calculated that △K2 is 50% greater than △K1, which means that the temperature sensitivity of the electrode can be effectively reduced by using the polymer microspheres of the present invention in the outer membrane of the glucose electrochemical sensor.
[0076] Table 1: Test response current values of sensing electrodes E1 and E2 at different temperatures and different glucose concentrations
[0077]
[0078] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0079] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A polymer film for a biosensor, characterized in that: The polymer membrane is a two-phase cross-linked polymer membrane, wherein the first phase is a polymer body and the second phase is polymer microspheres, the polymer body is an amphiphilic cross-linked polymer, and the polymer microspheres are hydrophobic cross-linked polymers; the amphiphilic cross-linked polymer consists of a hydrophilic component, a hydrophobic component and a cross-linking agent A.
2. The polymer film according to claim 1, characterized in that The hydrophobic monomer in the hydrophobic cross-linked polymer includes at least one of styrene, methyl methacrylate, glycidyl methacrylate, glycidyl acrylate, methyl acrylate, butyl methacrylate, butyl acrylate, ethyl methacrylate, ethyl acrylate, phenylethyl methacrylate, phenylethyl acrylate, phenoxyethyl methacrylate, phenoxyethyl acrylate, tert-butyl methacrylate, tert-butyl acrylate, 2-vinylpyridine, 4-vinylpyridine, ethoxyethyl methacrylate and ethoxyethyl acrylate.
3. The polymer film according to claim 1, characterized in that The hydrophilic component is at least one of polyethylene glycol, polyethylene methacrylate, poly N-vinyl pyrrolidone, polyvinyl alcohol, polyacrylamide, poly N, N-dimethylacrylamide, polyacrylic acid, sodium polystyrene sulfonate, poly hydroxyethyl methacrylate and poly hydroxyethyl acrylate.
4. The polymer film according to claim 1, characterized in that The hydrophobic component is at least one of polystyrene, polymethyl methacrylate, polymethyl acrylate, polybutyl methacrylate, polybutyl acrylate, polyethyl methacrylate, polyethyl acrylate, polyphenylethyl methacrylate, polyphenylethyl acrylate, polyphenoxyethyl methacrylate, polyphenoxyethyl acrylate, polytert-butyl methacrylate, polytert-butyl acrylate, poly-2-vinylpyridine, poly-4-vinylpyridine, polyethoxyethyl methacrylate and polyethoxyethyl acrylate.
5. The polymer film according to claim 1, characterized in that The crosslinking agent A is one of polyethylene glycol diglycidyl ether, adipic acid, hexamethylenediamine or glutaraldehyde.
6. The polymer film according to claim 1, characterized in that In the amphiphilic cross-linked polymer, the mass content of the cross-linking agent is 1% to 10%, the mass content of the hydrophilic component is 20% to 50%, and the mass content of the hydrophobic component is 40% to 79%.
7. The polymer film according to claim 1, characterized in that The polymer microspheres have a diameter of 0.1 um to 1 um, preferably 0.2 um to 0.5 um.
8. The method for preparing a polymer film according to any one of claims 1 to 7, characterized in that: The following steps are involved: A. Preparation of polymer microspheres 1) Add the hydrophobic monomer and the crosslinking agent B into ultrapure water, and deoxygenate by blowing high-purity nitrogen gas; 2) Add a water-soluble initiator and stir to dissolve it; 3) Place in a 70-90°C oil bath and heat with stirring for 20-30 hours; 4) centrifuging, washing and drying the product to obtain a solid powder; B. Introduction of amphiphilic cross-linked polymers 1) dissolving the amphiphilic cross-linked polymer and the cross-linking agent in an organic solvent; 2) adding the prepared solid powder and subjecting it to ultrasonic dispersion treatment to obtain a polymer film.
9. The preparation method according to claim 8, characterized in that: In step A), the initiator is at least one of potassium persulfate and ammonium persulfate; the crosslinking agent B includes at least one of 1,4-divinylbenzene, 1,4-butanediol dimethacrylate, 1,3-propylene glycol dimethacrylate, 1,4-butanediol diacrylate, and 1,3-propylene glycol diacrylate.
10. A glucose biosensor, characterized in that: The invention comprises the polymer film according to any one of claims 1 to 7.